Mechanosensitive channel Piezo1 is an essential regulator in cell cycle progression of optic nerve head astrocytes. Issue 5 (4th January 2023) - Wan, Yue; Wang, Haiping; Fan, Xiaowei; Bao, Jiayu; Wu, Shen; Liu, Qian; Yan, Xuejing; Zhang, Jingxue; Jin, Zi‐bing; Xiao, Bailong; Wang, Ningli
Abstract: Optic nerve head (ONH) astrocytes provide structural and metabolic support to neuronal axons in developmental, physiological, and pathological progression. Mechanosensitive properties of astrocytes allow them to sense and respond to mechanical cues from the local environment. We confirmed that ONH astrocytes express the mechanosensitive ion channel Piezo1 in vivo. By manipulating Piezo1 knockdown or overexpression in vitro, we found that Piezo1 is necessary but insufficient for ONH astrocyte proliferation. Loss of Piezo1 can lead to cell cycle arrest at G0/G1 phase, a possible mechanism involving decreased yes‐associated protein (YAP) nuclear localization and downregulation of YAP‐target cell cycle‐associated factors, including cyclin D1 and c‐Myc. Gene ontology enrichment analysis of differential expression genes from RNA‐seq data indicates that the absence of Piezo1 affects biological processes involving cell division. Our results demonstrate that Piezo1 is an essential regulator in cell cycle progression in ONH astrocytes. Main Points: The mechano‐transducer Piezo1 is essential for optic nerve head astrocyte proliferation. Loss of Piezo1 leads to cell cycle arrest through decreased yes‐associated protein (YAP)nuclear localization and downregulation of YAP‐target factors.